The impact of RADEC learning model on the problem-solving ability of high school students - Mallo, Bakri; Idris, Mustamin; Nurhayadi; Pathuddin; Dasa Ismaimuza (Universitas Papua, 2025)
The low learning outcomes and problem-solving abilities of students in Palu City are the driving force for finding a student-centered learning model that can improve the problem-solving abilities of high school students in Palu City. This research method is a quasi-experimental design with an intact group comparison design consisting of two groups, namely the experimental class with the RADEC Model learning treatment with a differentiated learning strategy and the control class with direct learning models. The study population was 3656 students, while the sample was 186 students in the experimental class and 186 students in the control class. The researcher selected the sample by purposive random sampling technique. The instruments used were problem-solving ability tests and learning style questionnaires. Data were analyzed using t-test statistics and two-way ANOVA. The results showed that the RADEC learning model with a differentiated learning strategy had a greater impact when compared to the direct instruction model on the mathematical problem-solving abilities of high school students in Palu City, with a significance value of p = 0.000. The average score of problem-solving ability of students who follow the RADEC learning model is 79.63. While the average score of problem solving of students who follow the direct instruction model is 50.72 that the difference in the impact of the learning model is 28.91. The RADEC learning model does not have a different impact on the mathematical problem-solving ability of high school students in Palu city based on learning styles, so that teachers can implement it in classes that have heterogeneous students in terms of learning styles.